The impact of mindfulness on well-being and performance in the workplace: an inclusive systematic review of the empirical literature. Issue 4 (4th July 2017) - Lomas, Tim; Medina, Juan Carlos; Ivtzan, Itai; Rupprecht, Silke; Hart, Rona; Eiroa-Orosa, Francisco José
ABSTRACT: Work can be demanding, imposing challenges that can be detrimental to the physical and mental health of workers. Efforts are therefore underway to develop practices and initiatives that may improve occupational well-being. These include interventions based on mindfulness meditation. This paper offers a systematic review of empirical studies featuring analyses of mindfulness in occupational contexts. Databases were reviewed from the start of records to January 2016. Eligibility criteria included experimental and correlative studies of mindfulness conducted in work settings, with a variety of well-being and performance measures. A total of 153 papers met the eligibility criteria and were included in the systematic review, comprising 12, 571 participants. Mindfulness was generally associated with positive outcomes in relation to most measures. However, the quality of the studies was inconsistent, so further research is needed, particularly involving high-quality randomized control trials.